Explaining the trends in breastfeeding behaviours in Great Britain: Findings from the Infant Feeding Surveys, 1985 to 2010 - Simpson, D (2017)
Available data from the quinquennial Infant Feeding Surveys (IFS) show that breastfeeding rates in Great Britain (GB) rose steadily between 1985 and 2010. However, the rates of breastfeeding continuation and exclusivity remain relatively low, and there is evidence that breastfeeding in public may still be considered unacceptable by many in GB. To date, no study has examined the reasons behind the increase in breastfeeding rates between 1985 and 2010, and the factors which influence women’s practice of breastfeeding in public in GB remain under-researched. Therefore, this DPhil research aimed to investigate whether the increase in breastfeeding rates in the first six weeks after childbirth in GB between 1985 and 2010 were driven by changes in the distribution of population characteristics, or changes in the differences in breastfeeding behaviours between subgroups of women. It also aimed to investigate the factors which influenced the practice of breastfeeding in public in GB in 1995 to 2010. Data from the IFS surveys in 1985 to 2010 were analysed to, firstly, describe and summarise the distribution of selected explanatory factors among the childbearing population of GB from 1985 to 2010. This was followed by an estimation of the independent effects of these explanatory factors on breastfeeding initiation, breastfeeding continuation at one week and at six weeks, and breastfeeding in public, in each survey year. There was an assessment of the changes over time in the effects of each factor on breastfeeding initiation, and on breastfeeding continuation at one week and at six weeks. This was followed by an examination of the extent to which changes in the distribution of factors among the childbearing population contributed to the increase in breastfeeding rates in the first six weeks in GB between 1985 and 2010. This DPhil research found no evidence of changes in the effects of factors on breastfeeding in the first six weeks between 1985 and 2010. This suggests that breastfeeding behaviours had not improved over time. At the same time, there were increases in the distribution of those factors which positively influence breastfeeding, suggesting that the increase in breastfeeding rates in the first six weeks between 1985 and 2010 were indeed attributable to population changes rather than improved breastfeeding behaviours. Additionally, breastfeeding in public was seemingly most influenced by women’s perceptions of the normality and acceptability of breastfeeding in GB. There is a clear need for more equitable interventions to target the needs and perceptions of those women in GB who remain characteristically less likely to breastfeed.